Determining the markers of a preference for imaginary worlds fiction calls for comparisons across kinds of fiction readers and forms of exploration. (18th November 2022) - Winner, Ellen
Abstract: The authors do not compare readers who prefer imaginary world fiction to readers with other reading preferences, failing to rule out the hypothesis that their findings apply to all readers. The authors also do not test their hypotheses against plausible alternative ones, several of which are suggested here.